The effect of hydrostatic pressure on thermodynamic characteristics of NH₃CH₂COOH·H₂PO₃ type ferroelectric materials - Zachek, I.R.; Levitskii, R.R.; Vdovych, A.S. (Condensed Matter Physics, 2017)
The model of NH₃CH₂COOH·H₂PO₃, modified by taking into account the piezoelectric coupling between the ordering structure elements and the strains εi , εj , is used for investigation of the effects that appear under external pressures. Within two-particle cluster approximation, the components of polarization vector and static dielectric permittivity tensor of the mechanically clamped and free crystals, their piezoelectric and thermal characteristics are calculated. The effect of hydrostatic pressure on the phase transition and the calculated physical characteristics of the crystal is studied. A good quantitative description of experimental data for these crystals is obtained.